Mechanism and therapeutic implications of pomalidomide-induced immune surface marker upregulation in EBV-positive lymphomas - Jaeger, Hannah K.; Davis, David A.; Nair, Ashwin; Shrestha, Prabha; Stream, Alexandra; Yaparla, Amulya; Yarchoan, Robert (Scientific reports, 2023)
Epstein-Barr virus (EBV) downregulates immune surface markers to avoid immune recognition. Pomalidomide (Pom) was previously shown to increase immune surface marker expression in EBV-infected tumor cells. We explored the mechanism by which Pom leads to these effects in EBV-infected cells. Pom increased B7-2/CD86 mRNA, protein, and surface expression in EBV-infected cells but this was virtually eliminated in EBV-infected cells made resistant to Pom-induced cytostatic effects. This indicates that Pom initiates the upregulation of these markers by interacting with its target, cereblon. Interestingly, Pom increased the proinflammatory cytokines IP-10 and MIP-1∝/β in EBV infected cells, supporting a possible role for the phosphoinositide 3-kinase (PI3K)/AKT pathway in Pom’s effects. Idelalisib, an inhibitor of the delta subunit of PI3 Kinase, blocked AKT-Ser phosphorylation and Pom-induced B7-2 surface expression. PU.1 is a downstream target for AKT that is expressed in EBV-infected cells. Pom treatment led to an increase in PU.1 binding to the B7-2 promoter based on ChIP analysis. Thus, our data indicates Pom acts through cereblon leading to degradation of Ikaros and activation of the PI3K/AKT/PU.1 pathway resulting in upregulation of B7-2 mRNA and protein expression. The increased immune recognition in addition to the increases in proinflammatory cytokines upon Pom treatment suggests Pom may be useful in the treatment of EBV-positive lymphomas.